International financial linkages of Latin American banks: the effects of political risk and deposit dollarisation - Francisco Ramon-Ballester; Torsten Wezel (European Central Bank (ECB), 2007)
This paper empirically investigates the extent to which the financial linkages of Latin American banks with the exterior are influenced by political risk and deposit dollarisation. We find that the sum of banks' foreign assets and liabilities is a function of risk-return considerations and excess domestic credit demand. An increase in political risk is shown to be associated with a build-up of foreign positions by the banking sector, but this adverse effect on the banking system is mitigated in economies with a high share of dollarised deposits. These relationships largely hold when the determinants of foreign assets and liabilities are estimated separately, with risk-induced capital flight being moderated by a high degree of deposit dollarisation. While changes in overall country risk including the risk of macro collapse drive official capital outflows, for a wider measure of capital flight including informal flows only changes in political risk matter. In each case, deposit dollarisation is shown to possess a risk-mitigating property. The results suggest caution with active dedollarisation strategies in highly dollarised economies where political instability remains an issue.
Keywords: E42; F36; G21; 330; banking systems; dollarisation; financial integration; Latin America; political risk; Bank; Währungssubstitution; Internationaler Finanzmarkt; Lateinamerika